2017
DOI: 10.1016/j.soard.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and lifestyle factors as determinants of energy intake and macronutrient composition: a 10-year follow-up after bariatric surgery

Abstract: Background Early identification of the potential to adopt an unhealthy diet, long-term, could improve weight outcomes for patients having undergone bariatric surgery. Objectives We explored whether pre-surgical sociodemographic and lifestyle characteristics, together with the type of surgery, could predict 10-year changes in dietary intake following bariatric surgery. Setting Surgical departments and primary health care centers, nationwide. Methods Participants were from the Swedish Obese Subjects study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…A recent French retrospective study, including 16,620 patients who underwent bariatric surgery since 2009, found in a multivariable analysis that male sex, young age, no diagnosis of T2DM and poor 1 year follow-up was a predictor of poor 5-year follow-up ( 70 ). In studies with follow-up until 10 years after bariatric surgery, male sex was associated with an unfavorable energy and macronutrient intake and higher alcohol intake, which was also shown for younger age and sedentary behavior before surgery ( 71 ). Furthermore, male sex was associated with higher weight regain after RYGB procedure, next to other factors as white ethnicity and higher socioeconomic status ( 72 ).…”
Section: Interventionsmentioning
confidence: 97%
“…A recent French retrospective study, including 16,620 patients who underwent bariatric surgery since 2009, found in a multivariable analysis that male sex, young age, no diagnosis of T2DM and poor 1 year follow-up was a predictor of poor 5-year follow-up ( 70 ). In studies with follow-up until 10 years after bariatric surgery, male sex was associated with an unfavorable energy and macronutrient intake and higher alcohol intake, which was also shown for younger age and sedentary behavior before surgery ( 71 ). Furthermore, male sex was associated with higher weight regain after RYGB procedure, next to other factors as white ethnicity and higher socioeconomic status ( 72 ).…”
Section: Interventionsmentioning
confidence: 97%
“…Obesity is a chronic disease that affects millions of individuals and its incidence has been increased in pandemic proportions 27 . Bariatric surgery is considered the most effective treatment, resulting in significant weight loss, as well as improvement of associated comorbidities 18 , 19 . Considering surgical techniques, Roux-en-Y gastric bypass (RYGB) is the most commonly performed surgical procedure 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that little information was available about the form of questionnaires used. Five studies [ 66 , 69 , 71 , 93 , 120 ] used the Swedish Obese Subjects (SOS) study questionnaire [ 132 ] ( Table 3 ), which was adapted from a simplified dietary history interview and was previously validated using a 4-day FR, nitrogen urinary excretion and 24 h energy expenditure measured by indirect calorimetry in obese and non-obese population, but not in bariatric population.…”
Section: Resultsmentioning
confidence: 99%